Prevalence and Incidence of Antimicrobial-Resistant Organisms among Hospitalized Inflammatory Bowel Disease Patients - Alon Vaisman; Kevin Pivovarov; Allison McGeer; Barbara Willey; Bjug Borgundvaag; Vanessa Porter; Piraveina Gnanasuntharam; Yanliang Wei; Geoffrey C Nguyen (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Patients with inflammatory bowel disease (IBD) experience frequent hospitalizations and use of immunosuppressive medications, which may predispose them to colonization with antimicrobial-resistant organisms (ARO).